Pluripotency Associated Genes Are Reactivated by Chromatin-Modifying Agents in Neurosphere Cells - David Ruau; Roberto Enseñat‐Waser; Timo C. Dinger; Duttu S. Vallabhapurapu; Alexandra Rolletschek; Christine Hacker; Thomas Hieronymus; Anna M. Wobus; Albrecht Müller; Martin Zenke (2008)
Abstract Chromatin architecture in stem cells determines the pattern of gene expression and thereby cell identity and fate. The chromatin-modifying agents trichostatin A (TSA) and 5-Aza-2′-deoxycytidine (AzaC) affect histone acetylation and DNA methylation, respectively, and thereby influence chromatin structure and gene expression. In our previous work, we demonstrated that TSA/AzaC treatment of neurosphere cells induces hematopoietic activity in vivo that is long-term, multilineage, and transplantable. Here, we have analyzed the TSA/AzaC-induced changes in gene expression by global gene expression profiling. TSA/AzaC caused both up- and downregulation of genes, without increasing the total number of expressed genes. Chromosome analysis showed no hot spot of TSA/AzaC impact on a particular chromosome or chromosomal region. Hierarchical cluster analysis revealed common gene expression patterns among neurosphere cells treated with TSA/AzaC, embryonic stem (ES) cells, and hematopoietic stem cells. Furthermore, our analysis identified several stem cell genes and pluripotency-associated genes that are induced by TSA/AzaC in neurosphere cells, including Cd34, Cd133, Oct4, Nanog, Klf4, Bex1, and the Dppa family members Dppa2, 3, 4, and 5. Sox2 and c-Myc are constitutively expressed in neurosphere cells. We propose a model in which TSA/AzaC, by removal of epigenetic inhibition, induces the reactivation of several stem cell and pluripotency-associated genes, and their coordinate expression enlarges the differentiation potential of somatic precursor cells. Disclosure of potential conflicts of interest is found at the end of this article.